Novel hypotheses related to Temporomandibular joint derived from Ankylosing spondylitis. (November 2020) - Shadamarshan Rengasayee, Arunkumar; Roy Chowdhury, Sanjay Kumar; Sharma, Rohit; Padma Priya, Sivan
Abstract: Ankylosing spondylitis (AS) is a seronegative arthropathy that affects fibrocartilaginous joints leading to arthritis and eventually ankylosis. Temporomandibular joint (TMJ), a fibrocartilaginous joint is affected to a lesser extent than the other joints, very rarely precipitating TMJ ankylosis. No explanation exists for the same in the present literature. Several hypothesis have been presented to explain this phenomenon of rarity of TMJ ankylosis in AS. The presence of an intraarticular disc acts as a physical barrier to the ankylotic process. However, in cases with AS, that present with TMJ ankylosis, this hypothesis needs several clarifications since the intraarticular disc is a constant phenomenon in TMJ. The cause of TMJ ankylosis in these cases might be explained by two hypotheses. Firstly, Pathological condylar loading in some cases; secondly, an application of the orthopaedic concept of functional enthesis to the TMJ disc and thirdly, an application of the concept of enthesis organ to TMJ. Using these hypotheses, important concepts on the anatomy and evolution of TMJ can be derived with evidence from literature. The intraarticular disc may be considered as an involuted tendon of the lateral pterygoid muscle which not only attaches to the mandibular condyle but also to the temporal bone via a elastic fiber mediated enthesis extending to the malleus through the discomalleolar ligament. The fibrocartilaginous changes that occur on the undersurface of the disc may support the concept of functional enthesis and provide a reverse evidence for the disc being a tendon. The evidence presented from extant monotremes may also throw light on the embryological development of the articular disc. These evidences are more of an anecdote than being focussed. Several scientific experiments, studies and data collection needs to be carried out to validate them. The proof of these hypotheses will be of use in establishing the development and role of the articular disc in TMJ function and TMJ disorders, including AS. The understanding of the role of the articular disc is important since many firstly, TMJ disorders are being treated by discectomy with good results, apparently rendering the disc vestigial and secondly, in the era of tissue engineering where efforts are being made to artificially produce articular disc and its analogues.